(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Gamification has emerged as an innovative pedagogical approach in English as a Second Language (ESL) and English as a Foreign Language (EFL) education, integrating game design elements to enhance learner engagement, motivation, and language retention. This article is discussed about gamification in teaching.